Diaspora Conversions : Black Carib Religion and the Recovery of Africa - Johnson, Paul C. (Paul Christopher), 1964- (Book collections on Project MUSE., 2007)
By joining a diaspora, a society may begin to change its religious, ethnic, and even racial identifications by rethinking its ""pasts."" This pioneering multisite ethnography explores how this phenomenon is affecting the remarkable religion of the Garifuna, historically known as the Black Caribs, from the Central American coast of the Caribbean. It is estimated that one-third of the Garifuna have migrated to New York City over the past fifty years. Paul Christopher Johnson compares Garifuna spirit possession rituals performed in Honduran villages with those conducted in New York, and what emer